Triple Cross [large type] - Patterson, James, 1947- (Patterson, James, 1947- Alex Cross series., 2022)
"Detective Alex Cross hunts down a serial killer who targets entire families--and who will next be coming for the Crosses. A methodical killer is targeting multigenerational families in and around Washington, DC--striking under cover of darkness, triggering no alarms, leaving no physical evidence of any kind. Alex isn't the only one investigating. Also on the case is a charismatic true-crime author who sees patterns the detectives miss. The writer calls 'The Family Man' a perfect crime story. Alex knows there is no perfect crime--the investigation should never become the story. Unless the ending falls somewhere between fact and fiction"--